Crowd theory in some modern fiction: Dickens, Zola and Canetti, 1841-1960 - Maia, Rousiley Celi Moreira (1992)
This thesis examines some perceptions of collective behaviour and psychology in some nineteenth and twentieth century literature. Focusing on selected works by three novelists, Charles Dickens's Barnaby Rudge (1841) and A Tale of Two Cities (1859), Emile Zola's Germinal (1885) and Elias Canetti's Auto-da-Fe (1935), it is an attempt to analyse the cultural representations of the nature, psychology and behaviour of crowds from 1841-1960.